Estimating proton beam therapy utilization and Investment in Thailand - Chitapanarux, Imjai; Tharavichitkul, Ekkasit; Prayongrat, Anussara; Sripan, Patumrat; Zubizarreta, Eduardo; Anacak, Yavuz; Siraprapasiri, Pathomphorn; Tungkasamit, Tharatorn; Changmanee, Chonsanee (Frontiers in Public Health, 2025)
BackgroundThailand’s first Proton Beam Therapy (PBT) center became operational in August 2021. Given the high costs and specialized expertise required, evaluating the clinical and economic implications of PBT and planning for its expansion are essential for Thailand’s healthcare system.MethodsThis study projected national PBT demand using data from the Thai PBT center, the Thai Association of Radiation Oncology (THASTRO), national cancer registry reports (Volumes VIII–X), and GLOBOCAN (2022–2040). The number of cancer patients requiring PBT was estimated based on: (1) Thailand’s Comptroller General’s Department (CGD) reimbursement guidelines (June 2023), and (2) the American Society for Radiation Oncology (ASTRO) model policy. Infrastructure, personnel, and cost data were collected, with resource gaps assessed using RRCC version 24.ResultsBetween 2022 and 2023, the first PBT center treated 628 patients—approximately 7% of all radiotherapy cases. Under CGD’s limited reimbursement criteria, an estimated 1,454–2,797 patients per year would be eligible for PBT, corresponding to a need for 3–5 PBT units. However, when reimbursement constraints are excluded, this estimate increases to 6–10 units. The ASTRO model suggests even broader eligibility, with 4,471–5,430 patients requiring 10–20 units. The cost of a basic PBT unit is estimated at USD $30 million (excluding building infrastructure), with a treatment course costing approximately $38,000 (RRCC v.24).ConclusionThe gap between reimbursement- and need-based demand highlights the tension between clinical benefit and cost. Strategic planning must balance equitable access, financial sustainability, and future growth of PBT in Thailand.